Financial Accounting - Pyle, W. W., Larson K. D. (London : Irwin, 1983)
This book is expected to provide the textual materials for the first semester accounting course at college and university level. The book further highlights instruments on business organisation, typical practices and legal, and financial statement.
Includes index
jbi, 21/03/2018
Loans
Keywords: accounting; Financial-accounting